PENGEMBANGAN DESAIN PEMBELAJARAN INTERAKTIF BERBASIS TEKNOLOGI UNTUK MENINGKATKAN KETERLIBATAN SISWA - Ramlan Setiawan; Roby Zamzam Rafsanjani; Selamet (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of digital technology has had a significant impact on education, particularly in terms of innovation in learning design. This study aims to develop a technology-based interactive learning design that can increase student engagement in the learning process. The research method used is research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The study subjects consisted of high school students participating in technology-based learning in several subjects. Data were obtained through observations, interviews, and questionnaires to measure student engagement levels before and after the implementation of the learning design. The results show that technology-based interactive learning design can increase student active participation, strengthen conceptual understanding, and create a collaborative and enjoyable learning environment. Interactive features such as digital simulations, online quizzes, and learning management systems (LMS) have proven effective in increasing student motivation and attention. Thus, the development of technology-based interactive learning design is an important strategy in supporting the transformation of 21st-century education that emphasizes creativity, collaboration, and independent learning.